2014
DOI: 10.4317/jced.51415
|View full text |Cite
|
Sign up to set email alerts
|

The role of topical simvastatin on bone regeneration: A systematic review

Abstract: Objectives: The aim of this systematic review was to summarize the results concerning the use of simvastatin for promoting bone regeneration and to discuss the level of scientific evidence supporting such findings. Material and Methods: A Pubmed search using “Simvastatin”[Mesh] AND “Bone Regeneration”[Mesh] as Boolean operators was constrained to the last 10 years and only included papers written in English. Results: Of the 41 relevant papers reviewed, most of them (76.2%) have been published in the last 5 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 36 publications
1
14
0
3
Order By: Relevance
“…Masuzaki et al gave a single injection of fluvastatin impregnated microspheres to rats with tibial titanium implants, this demonstrated enhanced bone growth and bone contact at 14 days as demonstrated by staining and microscopy around the implant and was accompanied by an increased bending strength, as measured by extraction of the femur following implantation at 2 or 4 weeks after surgery followed by three point bending with a universal testing machine 33 . Similar studies have reported encouraging results with simvastatin coated implants, scaffolds and biomaterials 34,35 . Topical application of statins may therefore confer the potential beneficial osteogenic effects outlined previously but Osseointegration generally occurs within 3 months of primary arthroplasty 36,37 .…”
Section: Statins and Osseointegration Of Prosthetic Implants And Bonesupporting
confidence: 69%
“…Masuzaki et al gave a single injection of fluvastatin impregnated microspheres to rats with tibial titanium implants, this demonstrated enhanced bone growth and bone contact at 14 days as demonstrated by staining and microscopy around the implant and was accompanied by an increased bending strength, as measured by extraction of the femur following implantation at 2 or 4 weeks after surgery followed by three point bending with a universal testing machine 33 . Similar studies have reported encouraging results with simvastatin coated implants, scaffolds and biomaterials 34,35 . Topical application of statins may therefore confer the potential beneficial osteogenic effects outlined previously but Osseointegration generally occurs within 3 months of primary arthroplasty 36,37 .…”
Section: Statins and Osseointegration Of Prosthetic Implants And Bonesupporting
confidence: 69%
“…12 Besides its lipid-lowering effects, simvastatin can also modulate bone regeneration process at both molecular and cellular levels by participating in activation of osteoblast and inhibition of osteoclast. 13 Moreover, simvastatin could not only inhibit 3-hydroxy-3-methylglutarylcoenzyme A reductase and the mevalonic acid pathway but also increase the osteoprotegerin expression to antagonize osteoclasts. 14 Nylestriol, a derivative of long-acting estriol and a kind of lente estrogen, was synthesized in China in 1984.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 This class of drug can inhibit HMG-CoA reductase from turning into mevalonic acid, and is widely used for hyperlipidemia treatment. 1,2 Several researchers have demonstrated that SV has pleiotropic effects, including anti-inflammatory action, 2,3 induces angiogenesis and improves the function of endothelial cells, 4,5,6,7,8 as well as enhancing the synthesis and mineralization of bone 9,10,11,12,13 and dentin 6,14,15,16,17 matrices. The pathway for SV mediating osteo/odontogenic differentiation is not fully known.…”
Section: Introductionmentioning
confidence: 99%